Desmoid tumor at the gastrointestinal anastomosis after a one-anastomosis gastric bypass (mini-gastric bypass): a case report - Mahnashi, Yasir (J Surg Case Rep, 2020)
Desmoid tumors of the small bowel wall are rare tumors of the gastrointestinal tract. The signs and symptoms ranging from non-specific to severe abdominal pain to the sensation of a mass and abdominal fullness. We present the case of a 48-year-old man who presented 3 years post-one-anastomosis gastric bypass (mini-gastric bypass) with vague abdominal pain and early satiety of one-month duration. A CT scan of the abdomen revealed a well-defined compressive mass in the left hypochondrium. A laparoscopic exploration was performed, but it was converted into a laparotomy due to the huge size of the mass. The desmoid tumor at the gastrojejunal anastomosis was resected, followed by a Roux-en-Y reconstruction. The patient’s postoperative course was uneventful, and he was discharged on the seventh day post-operation. He did not show any signs or symptoms suggestive of complications or recurrence during his follow-up.